APOEɛ4 Allele Moderates the Association Between Basal Forebrain Nuclei Volumes and Allocentric Navigation in Older Adults Without Dementia - Lerch, Ondřej; Laczó, Martina; Vyhnálek, Martin; Nedelská, Zuzana; Hort, Jakub; Laczó, Jan (Journal of Alzheimer's disease, 2022)
BACKGROUND: Cholinergic deficit and medial temporal lobe (MTL) atrophy are hallmarks of Alzheimer's disease (AD) leading to early allocentric spatial navigation (aSN) impairment. APOEɛ4 allele (E4) is a major genetic risk factor for late-onset AD and contributes to cholinergic dysfunction. Basal forebrain (BF) nuclei, the major source of acetylcholine, project into multiple brain regions and, along with MTL and prefrontal cortex (PFC), are involved in aSN processing. OBJECTIVE: We aimed to determine different contributions of individual BF nuclei atrophy to aSN in E4 positive and E4 negative older adults without dementia and assess whether they operate on aSN through MTL and PFC or independently from these structures. METHODS: 120 participants (60 E4 positive, 60 E4 negative) from the Czech Brain Aging Study underwent structural MRI and aSN testing in real-space arena setting. Hippocampal and BF nuclei volumes and entorhinal cortex and PFC thickness were obtained. Associations between brain regions involved in aSN were assessed using MANOVA and complex model of mutual relationships was built using structural equation modelling (SEM). RESULTS: Path analysis based on SEM modeling revealed that BF Ch1-2, Ch4p, and Ch4ai nuclei volumes were indirectly associated with aSN performance through MTL (pch1 - 2 = 0.039; pch4p = 0.042) and PFC (pch4ai = 0.044). In the E4 negative group, aSN was indirectly associated with Ch1-2 nuclei volumes (p = 0.015), while in the E4 positive group, there was indirect effect of Ch4p nucleus (p = 0.035). CONCLUSION: Our findings suggest that in older adults without dementia, BF nuclei affect aSN processing indirectly, through MTL and PFC, and that APOE E4 moderates these associations.
Keywords: senioři; pars basalis telencephali; alely; Alleles; basal forebrain; cholinergní látky; hippocampus; Alzheimer Disease; magnetic resonance imaging; atrofie; Cholinergic Agents; entorhinal cortex; magnetická rezonanční tomografie; Allocentric spatial navigation; Magnetic Resonance Imaging; Humans; Basal Forebrain; Alzheimerova nemoc; apolipoprotein E; Aged; prefrontal cortex; lidé; Atrophy